Clinical and genetic spectrum of epileptic encephalopathies in Egyptian infants and children - Nour Mohamed Mohsen Ahmed Elkhateeb; Joseph Gleeson; Laila Abdelmotaleb Selim; Marian Yousry Fahmy (Cairo : Nour Mohamed Mohsen Ahmed Elkhateeb, 2015)
Epileptic encephalopathies are a group of conditions in which cognitive, sensory, and/or motor functions deteriorate as a consequence of epileptic activity. The clinical and EEG characteristics of these conditions depend on the age at onset, and may change over time, according to the successive age ranges. Etiologies for epileptic encephalopathies include genetic and metabolic etiologies, CNS malformations and acquired CNS insults. To evaluate the genetic basis of epileptic encephalopathies in Egyptian children, to outline the main clinical, neurophysiological and MRI characteristics and to correlate between clinical phenotype and neurophysiological findings in this group of disorders. An analytical study that included fifty patients who were all eligible children fulfilling the inclusion criteria, attending neurology, neurometabolic outpatient clinics, at Cairo university children hospital, and the neurogenetic clinic at the national research center during the study period (March 2014 to November 2015). Out of 50 patients studied; 7 patients (14 %), presented with early myoclonic epileptic encephalopathy, 11 patients (22 %) with early infantile epileptic encephalopathy, 9 patients (18 %) with West syndrome. Dravet syndrome was diagnosed in 6 patients (12 %), late infantile epileptic encephalopathy in one patient (2%), Lennox Gastaut syndrome in 8 patients (16%), Doose syndrome in 3 patients (6 %) and 5 patients (10%) could not be classified into a specific epileptic syndrome. 14 out of 50 patients had a definite aetiologic diagnosis;. 4 patients (8%) had genetic etiology including EXOC 2, MRPL19, EXOSC7, SCN1A and SCN2A mutations, 8 patients (16%) had inborn error of metabolism and 2 patients (4%) had CNS malformations including hemimegalencephaly and pontocerebellar hypoplasia. 3 patients (6%) had a potentially treatable epileptic encephalopathy. Epileptic encephalopathies are a heterogenous group of disorders. Prompt diagnosis and early treatment of potentially treatable metabolic epilepsies is crucial to improve neurologic outcome and prevent disastrous neurologic sequalae
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Epileptic encephalopathies; Genetic spectrum; Pediatrics